TO SOLVING THE PROBLEM OF TRAINING WORKING PERSONNEL OF RUSSIA - S. A. Antonov (Вестник университета)
The relevance of solving the problem of reducing the personnel potential of workers in Russia has been substantiated. A brief overview of the most significant scientific sources over the past three years has been adduced. The consequences of reducing the working personnel from a number of Russian citizens and modern methods of compensating for low human potential have been analysed. The main demotivators of labor have been considered also and various options for solving the problem have been presented, such as: developing a regional social infrastructure and improving the moral condition of women; enhancing the training of working personnel based on the national historical features of Russia; development of interaction between the state, enterprises and young employees in order to form the personnel potential of Russian workers. As a further area of research, the development of regional roadmaps for the regions of the Central Federal District has been proposed.